The Effect of Product Design and Price on Consumers’ Impulsive Buying on Shopee - Larasati, Dyah Ayu; Megasari, Aisyah Darti; Utomo, Priyo; Arifin, Syamsul; Nuryadi, Nuryadi (IJEBD (International Journal of Entrepreneurship and Business Development), 2025)
Purpose: This study aims to examine the effect of product design and price on consumers’ impulsive buying behavior on Shopee. Design/Methodology/Approach: The research employed a quantitative approach with purposive sampling of 200 respondents who had purchased sublimation-printed fabric products under the Cannamolid Pattern brand on Shopee. Data were collected through a five-point Likert scale questionnaire. The validity and reliability of the instrument were tested, and the data were analyzed using multiple linear regression with t-tests and F-tests through SPSS version 29. Findings: The results show that: (1) product design has a positive and significant effect on impulsive buying (? = 0.499; t = 14.237; p < 0.001); (2) price also has a positive and significant effect (? = 0.325; t = 9.284; p < 0.001); and (3) product design and price simultaneously have a significant effect on impulsive buying, with F = 188.603 and p < 0.001. The coefficient of determination (R²) of 0.657 indicates that both variables explain 65.7% of the variance in impulsive buying, while the remaining 34.3% is influenced by other factors outside the model. Research limitations/implications: This study emphasizes the role of product design and pricing strategies as strong triggers of impulsive buying in e-commerce. However, future research is recommended to include psychological factors and other marketing aspects for a more comprehensive understanding. Practical implications: The findings provide practical insights for e-commerce sellers, particularly local brands, to pay closer attention to product design and pricing strategies in order to stimulate consumers’ impulsive purchases. Originality/value: Few studies have specifically examined how product design—especially fabric motifs—and pricing strategies affect impulsive buying on e-commerce platforms such as Shopee. This study contributes a new perspective by highlighting the context of local MSMEs selling patterned fabric products, making the findings especially relevant for small businesses competing in Indonesia’s digital marketplace. Paper type: Research paper